Impact of smoking on the complement system: a narrative review - Alarabi, Ahmed B.; Alshbool, Fatima Z.; Khasawneh, Fadi T. (Frontiers in Immunology, 2025)
Smoking is a major cause of morbidity and mortality, resulting in an increased risk of cardiovascular, respiratory, inflammatory, and degenerative diseases. In this review, we highlight the complex interactions between smoking and activation of different components of the complement system, in order to underscore the notion that its dysregulation underlies—mechanistically—as well as exacerbates the progression of a host of disease processes. Moreover, we also briefly delve into components of tobacco smoke—including chemical constituents like tobacco glycoprotein (TGP) and particulate matter (PM), toxic metals, and other mainstream cigarette smoke chemicals—that have been identified as possible culprits in complement activation. In doing so, this review makes important and meaningful contributions to the ongoing efforts of combating the global health crisis posed by tobacco use, all while emphasizing the need for multifaceted strategies that include not only public health measures and educational efforts, but also innovative research that focuses on understanding and mitigating the biological mechanisms underlying smoking-related health conditions.